2023
DOI: 10.1002/adma.202303621
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Photoluminescence Efficiency of InAs Nanocrystals Synthesized with Aminoarsine via a ZnSe Thick‐Shell Overgrowth

Dongxu Zhu,
Houman Bahmani Jalali,
Gabriele Saleh
et al.

Abstract: InAs‐based nanocrystals can enable restriction of hazardous substances (RoHS) compliant optoelectronic devices, but their photoluminescence efficiency needs improvement. We report an optimized synthesis of InAs@ZnSe core@shell nanocrystals allowing to tune the ZnSe shell thickness up to seven mono‐layers (ML) and to boost the emission, reaching a quantum yield of ≈70% at ≈900 nm. It is demonstrated that a high quantum yield can be attained when the shell thickness is at least ≈3ML. Notably, the photoluminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…A true type-I offset is not observed. This can be the result of the small size of the InP core but is likely also the result of electric fields arising at the core–shell interface . Therefore, it is difficult to draw conclusions about the energy offset between the core and the shell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A true type-I offset is not observed. This can be the result of the small size of the InP core but is likely also the result of electric fields arising at the core–shell interface . Therefore, it is difficult to draw conclusions about the energy offset between the core and the shell.…”
Section: Resultsmentioning
confidence: 99%
“…This can be the result of the small size of the InP core but is likely also the result of electric fields arising at the core–shell interface. 48 Therefore, it is difficult to draw conclusions about the energy offset between the core and the shell. The coordination number for all In atoms is determined for this model, and it is found that four In atoms are undercoordinated.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of highquality InAs QDs has been reported and improved upon for more than 20 years, with much attention paid to the final monodispersity and less to the formation mechanisms. 20,26,41,42,[46][47][48][49][50][51]53 Most reported syntheses use indium carboxylate, a tertiary alkylphosphine, and a reactive silylarsine to nucleate and grow InAs QDs. In studying this precursor system, magic-sized clusters were observed as an intermediate with a characteristic absorption doublet with maxima at 425 and 460 nm.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One of the QD material systems known to form clusters but lacks structural characterization is InAs. The synthesis of high-quality InAs QDs has been reported and improved upon for more than 20 years, with much attention paid to the final monodispersity and less to the formation mechanisms. ,,,, , Most reported syntheses use indium carboxylate, a tertiary alkylphosphine, and a reactive silylarsine to nucleate and grow InAs QDs. In studying this precursor system, magic-sized clusters were observed as an intermediate with a characteristic absorption doublet with maxima at 425 and 460 nm. ,,, Even when investigating the usage of germylarsines to improve nanocrystal monodispersity, this characteristic cluster persists .…”
Section: Introductionmentioning
confidence: 99%
“…8–10 These QDs are usually prepared in a core–shell geometry, featuring excellent stability and efficient radiation. 11–15 One critical aspect that significantly affects their optoelectronic properties is the presence of trap states within the band gap, which lead to the localization of charge carriers. 16,17 These trap states are commonly associated with surface and interface defects.…”
Section: Introductionmentioning
confidence: 99%